Common Practices and Methodologies in Scientific Functional Characterization of Surface Topography - Abbass Walid; Matthias Eifler (Metrology)
More and more surfaces are required to fulfill functional characteristics that are embodied by their surface topography. In the process of measuring and characterizing the corresponding surfaces, many research activities have been conducted, and a broad variety of measuring principles and evaluation strategies have been developed. However, in industrial practice, there is still a lack of experience and a significant unhinged potential in this field. To predict which techniques will most likely be transferred more commonly into industrial applications, a study to identify the most frequently used measurement principles, methods, and surface texture parameters for characterizing functional surfaces through a systematic literature review of scientific research studies is conducted here. It can be shown that optical measuring instruments have emerged significantly, whereas the analysis is mostly performed using traditional and simple amplitude-based surface texture parameters. Based on the results, untapped potential in functional analysis can be revealed and the use of, e.g., function-oriented parameters or a direct measurement of the angular distribution can be recommended for a wider range of applications.